Liposomal Bupivacaine in Total Knee Arthroplasty for Better Postoperative Analgesic Outcome and Economic Benefits - Cherian, Jeffrey Jai; Muzaffar, Ali; Barrington, John W.; Elmallah, Randa D. K.; Chughtai, Morad; Mistry, Jaydev B.; Mont, Michael A. (The Journal of Knee Surgery, 2016)
When orthopedists consider which analgesia to use after total knee arthroplasty (TKA), the primary objective is to relieve pain with fewer adverse side effects. Over the last decade, substantial efforts have been made to improve pain control following TKA, but it is still very challenging to obtain optimal control. Current modalities in use, such as opioids, epidurals, and nerve blocks, provide substantial pain relief, but they are associated with substantial side effects and serious complications. Recently, bupivacaine, a commonly used nonopioid analgesic, has been formulated into an aqueous suspension of multivesicular liposomes that provide long-lasting analgesia, while avoiding significant adverse effects of opioids. The purpose of this review is to analyze the use of traditional postsurgical pain management and the potential contribution of a long-acting liposomal formulation of bupivacaine as part of the analgesic regimen in TKA, including its mode of action, injection technique, efficacy on pain, and health care costs.
Keywords: liposomal bupivacaine; total knee arthroplasty; analgesia; pain